2021
DOI: 10.1371/journal.pone.0255142
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated microRNA and mRNA signatures associated with overall survival in epithelial ovarian cancer

Abstract: Ovarian cancer (OC), the eighth-leading cause of cancer-related death among females worldwide, is mainly represented by epithelial OC (EOC) that can be further subdivided into four subtypes: serous (75%), endometrioid (10%), clear cell (10%), and mucinous (3%). Major reasons for high mortality are the poor biological understanding of the OC mechanisms and a lack of reliable markers defining each EOC subtype. MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate gene expression primarily by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…We found that the combined determination of the level of circulating miR-16-5p, miR-17-5p, miR-20a-5p and miR-93-5p circulating in blood plasma in patients with primary HGSOC tumors makes it possible to predict optimal cytoreduction with 80.1% sensitivity and 70% specificity (p = 0.022, TPR = 0.8, FPR = 0.3). Closer examination of the molecules, in particular, circulating miRNAs, that have already been identified in association with the mesenchymal subtype of HGSOC and poor overall survival [7,[106][107][108][109], in addition to our results, may reveal important information about the biology of unresectable HGSOC and can make a significant contribution to the creation of a test system for predicting suboptimal cytoreduction.…”
Section: Discussionsupporting
confidence: 55%
“…We found that the combined determination of the level of circulating miR-16-5p, miR-17-5p, miR-20a-5p and miR-93-5p circulating in blood plasma in patients with primary HGSOC tumors makes it possible to predict optimal cytoreduction with 80.1% sensitivity and 70% specificity (p = 0.022, TPR = 0.8, FPR = 0.3). Closer examination of the molecules, in particular, circulating miRNAs, that have already been identified in association with the mesenchymal subtype of HGSOC and poor overall survival [7,[106][107][108][109], in addition to our results, may reveal important information about the biology of unresectable HGSOC and can make a significant contribution to the creation of a test system for predicting suboptimal cytoreduction.…”
Section: Discussionsupporting
confidence: 55%